Associações esportivas e o poder Público de Maringá/PR: uma relação de dependência tutelar? - Silveira, Andrea Luiza Alves (2016)
The government of the Estado Novo, implemented by Getúlio Vargas, was governed by bureaucratic authoritarianism, populist and clientelism conduct that gave the sport a utilitarian character, salvationists and patronizing. Such practices established between the State and the Sports Field a dependent relationship protect surviving even after the promulgation of the Constitution of 1988, which rescued the guarantee of autonomy of sports institutions. During this period, especially from the 1990s, it began a major process of decentralization of social policies in Brazil, with the insertion of the market and the Third Sector in partnership with the State, to perform public services. To assist in understanding the current Brazilian sports model, both at the national level, as the state and municipal levels, the latter being the focus of this research, was made use of the contribution brought by the neo-corporatism theory, the theoretical framework of the Theory of Fields by Pierre Bourdieu and the Policy Analysis by Klaus Frey, to analyze the relationships established between the Municipal Government of Maringa/PR and Sports Associations (Third Sector) featuring traces of tutelary dependency. With the time frame the years 2005 to 2014, interviews were conducted semi-structured, then submitted to content analysis (Bardin, 2011), with the Secretaries of Sports and Leisure of the period and the representatives of the five Sports Associations whose modalities received more funds from the Incentive Program for Amateur Sport Maringa, namely: basketball, football, futsal, handball and volleyball. They were also analyzed documents available on the website of Municipal Transparency, financial reporting and the rules of sports which contributed in shaping current public policy maringaense sports. In parallel to the analysis, there was a historical contextualization of the Political- Bureaucratic Field in the city, seeking to identify the motivation for the creation of the Sports Associations and the trajectory of public and private stakeholders in this process. Three categories were obtained: administrative, technical/sporting and financial. First, the highlights were the recurrent problems of poor administrative management of Sports Associations, pointing to the need for proper training of both public officials, the private involved. Technical/sports category showed the existence of a sports capital by the coaches of Associations, considered better prepared than the coaches of the Sports and Recreation Department. The financial category was pronounced dependence of Sports Associations in relation to physical and financial resources of the Government, indicating that the maintenance of lending is a necessary condition for the survival of these institutions. Finally, despite the Sports Associations and Sports and Leisure Department have their strengths in this game, public policy has occurred and been sustained by relations of interdependence between these institutions.